2021
DOI: 10.1021/acsami.0c20288
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Constructing A Nano MOF-Derived Ni and CQD Embedded N-Doped Carbon Nanosphere for the Hydrogenation of Petroleum Resin at Low Temperature

Abstract: A key issue in attaining highly efficient supported catalysts for the hydrogenation of unsaturated polymers arises from the entanglement between the number of exposed active sites and the severe internal mass transfer limitation caused by their large molecular size. Hence, an ultrasmall N-doped carbon nanosphere with Ni NPs and CQDs embedded (Ni-CQDs/NCNs) was reasonably constructed by low-temperature (400 °C) pyrolysis of the precursor CQDs@Nano-Ni-ZIFs. As-prepared Ni-CQDs/NCNs exhibited superior catalytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…In addition to triggering defects and active sites in the carbon matrix, the doping of strongly coordinated heteroatoms, such as N and P, can also anchor MNPs as reaction centers. 158 By the DFT calculations results, Wu et al 76 found that the electronic regulation of N-doped carbon enhances the intrinsic activity of Ni in hydrogenation. Specifically, the Ni 6 cluster anchored on carbon (Ni 6 /C) and N-dope carbon (Ni 6 /NC) was designed as calculation modes (Figure 28a, b).…”
Section: ■ Mechanisms Of Heteroatom Dopingmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to triggering defects and active sites in the carbon matrix, the doping of strongly coordinated heteroatoms, such as N and P, can also anchor MNPs as reaction centers. 158 By the DFT calculations results, Wu et al 76 found that the electronic regulation of N-doped carbon enhances the intrinsic activity of Ni in hydrogenation. Specifically, the Ni 6 cluster anchored on carbon (Ni 6 /C) and N-dope carbon (Ni 6 /NC) was designed as calculation modes (Figure 28a, b).…”
Section: ■ Mechanisms Of Heteroatom Dopingmentioning
confidence: 99%
“…The zeolite imidazolate framework (ZIF), a promising candidate for the synthesis of metal/heteroatom-doped carbon catalysts, can easily control the doping of heteroatoms and design the morphology of carbon because of the periodic alternation of organic ligands and metal ions. As shown in Figure , N-doped carbons with CQDs and Ni NPs catalysts (Ni-CQDs/NC) were prepared by pyrolysis of CQDs@Nano-Ni-ZIFs precursors, which exhibited excellent catalytic activity of petroleum resin hydrogenation over a commercial Pd/C catalyst . The excellent catalytic performances of the catalysts are mainly attributed to the following aspects: (i) The ultrasmall structure (∼50 nm) improves the efficiency of internal mass transfer.…”
Section: Synthetic Approaches Of Metal/heteroatom-doped Carbon Catalystsmentioning
confidence: 99%
See 3 more Smart Citations